Reef sponges of the genus Agelas (Porifera: Demospongiae) from the Greater Caribbean - Parra-Velandia, Fernando J.; Zea, Sven; van Soest, Rob W. M. (Zootaxa, 2014)
The genus Agelas comprises a group of tropical and subtropical reef sponges that contains large, long-lived, often brightly colored and conspicuous species, distributed throughout the tropical western Atlantic, temperate northern Atlantic (Mediterranean Sea), and western and central Indo-Pacific Realms. Among tropical sponge genera, Agelas is one with similar species richness in the Greater Caribbean in comparison to the Indo Pacific. The presence of verticillated acanthostyle spicules and a fibroreticulate skeleton of spongin fibres cored and/or echinated by spicules characterize this group. Taxonomic identification relies on a combination of characters, where external morphology and color play a key role, owing to the paucity of microscopical characters. Thus, there is still a great deal of taxonomic confusion, even for the more common species. We carried out a detailed revision of Agelas species throughout the Greater Caribbean area using classic taxonomic tools. Samples and observations covered Colombia, Belize, Jamaica, the Bahamas, Barbados, Curaçao and Venezuela, and included type material from major museum collections. According to our results, the genus Agelas in the Caribbean has at least thirteen valid species, viz. Agelas sceptrum (Lamarck, 1815); A. dispar Duchassaing & Michelotti, 1864; A. dilatata Duchassaing & Michelotti, 1864; A. clathrodes (Schmidt, 1870); A. cervicornis (Schmidt, 1870); A. conifera (Schmidt, 1870); A. schmidti Wilson, 1902; A. tubulata Lehnert & van Soest, 1996; A. wiedenmayeri Alcolado, 1984; A. citrina Gotera & Alcolado, 1987; A. sventres Lehnert & van Soest, 1996; A. repens Lehnert & van Soest, 1998; and A. cerebrum Assmann et al., 2001. We found that variation of microscopic characteristics like skeleton arrangement, number of verticills and their spines, and spicule length and width, can be used as taxonomic tools, but only in a thorough comparison with other species in the same sub-regional context. Thus, a certain degree of familiarity with the genus’ regional variation is often required. The richness and distribution of these species in the Caribbean area show north/south differences and other ecological patterns are evident.